Botanical Medicine in Clinical Practice 2008
DOI: 10.1079/9781845934132.0547
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic botanical extracts.

Abstract: Plants have been used in the cure of diseases from the origins of humanity. It is commonly thought that traditionally used medicinal plants have already been tested and ratified because they have been considered effective medicines for so long and continue to be used as such with no or few side effects, and therefore are not in need of scientific evaluation. However, World Health Organization (WHO) specialists recommend that the traditional methods should be better investigated. To test medicinal plants, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Streptozotocin is known to reproduce the severe diabetes (glycemia above 300 mg/dL), and the plant extract could be more efficient treating individuals with a moderate diabetes (glycemia between 120 and 300 mg/dL). Previous studies testing plant extracts confirmed that animals with severe diabetes also presented no antidiabetic effect (Volpato et al 2007(Volpato et al , 2008(Volpato et al , 2011. The body weight loss represents one of the most common signs of diabetes.…”
Section: Bauhinia Holophylla In Diabetic Rats 269mentioning
confidence: 85%
See 1 more Smart Citation
“…Streptozotocin is known to reproduce the severe diabetes (glycemia above 300 mg/dL), and the plant extract could be more efficient treating individuals with a moderate diabetes (glycemia between 120 and 300 mg/dL). Previous studies testing plant extracts confirmed that animals with severe diabetes also presented no antidiabetic effect (Volpato et al 2007(Volpato et al , 2008(Volpato et al , 2011. The body weight loss represents one of the most common signs of diabetes.…”
Section: Bauhinia Holophylla In Diabetic Rats 269mentioning
confidence: 85%
“…Moreover, plants have been used as an alternative therapy for the diabetes treatment. Many plants present hypoglycemic activity, which were demonstrated experimentally in animals and humans, but some still require further investigation (Volpato et al 2002, Damasceno andVolpato 2008). Although several plants were tested for diabetes treatment, many of them were not evaluated, including species of the genus Bauhinia, popularly known as "cow's hoof" (Lorenzi and Matos 2002).…”
mentioning
confidence: 99%
“…Several herbal components (Damasceno and Volpato, 2008) and drugs (Cooppan, 2005;Davidson, 2001) have been used in an attempt to control diabetes and attenuate its complications during pregnancy in both women and experimental animals. Azadirachta indica A. Juss (Meliaceae), commonly called neem, is a tree native to India and Bhurma renowned for its medicinal properties.…”
Section: Introductionmentioning
confidence: 99%
“…From ancient times, plants have been used for treatment of Diabetes mellitus Damasceno and Volpato, 2008). The use of medicinal plants as alternative therapy is widely spread in the populations of underdeveloped countries, which have limited access to medical assistance.…”
Section: Introductionmentioning
confidence: 99%